2021
DOI: 10.1093/jcag/gwab027
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s and Colitis Canada’s 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: Executive Summary

Abstract: Persons with inflammatory bowel disease (IBD) make up more than 0.75% of the Canadian population in 2021. Early in the COVID-19 pandemic, individuals with IBD, particularly those on immunosuppressive therapies, were concerned that their health status may place them at higher risk of contracting COVID-19 or experiencing more severe disease course if infected with SARS-CoV-2. In response, Crohn’s and Colitis Canada developed the COVID-19 and IBD Taskforce in March 2020 to rapidly synthesize the evolving knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The COVID-19 literature search included studies published in 2021 or later, which updated the 2021 Impact of COVID-19 and IBD in Canada report. These dates were chosen to minimize overlap in identified studies with previous iterations of this impact report ( 1 , 4 ). Review topics, search terms, databases, and the exact date of the literature search for each review are specified in Supplementary Material 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 literature search included studies published in 2021 or later, which updated the 2021 Impact of COVID-19 and IBD in Canada report. These dates were chosen to minimize overlap in identified studies with previous iterations of this impact report ( 1 , 4 ). Review topics, search terms, databases, and the exact date of the literature search for each review are specified in Supplementary Material 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that full vaccination of two or three doses of RNA vaccine can significantly increase the level of neutralizing antibodies in the recipients, preventing the occurrence of a global pandemic amid the frequent emergence of new variants of SARS-CoV-2 both in adults and children [45] , [48] , [108] , [109] , [110] , [111] , [112] , [113] . Robust clinical data also confirmed that the COVID-19 vaccine is safe in children with specific diseases, including congenital immunodeficiency, congenital heart disease, pediatric inflammatory bowel disease and allergy [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] . Given that some parents are still hesitant about vaccine safety, reducing the single-dose volume of vaccines for children and extending the vaccination interval has been proven to reduce the occurrence of adverse events, which is expected to become the vaccination strategy for children in the future [111] , [123] , [124] .…”
Section: Why Children Should Be Vaccinated Against Covid-19?mentioning
confidence: 74%
“…They also indicated problems with postponed or rescheduled hospitalizations. Another published study also showed a significant decrease in hospitalizations in patients with IBD, mainly during the initial phase of the COVID-19 pandemic, primarily due to the heavy burden of patients with COVID-19 filling hospital beds [ 15 ]. It is remarkable that the incidence of hospitalization of patients with UC and CD has decreased considerably in the last decade, especially in patients under 40 years of age; therefore, it is not possible to say whether our results prove the impact of the pandemic on this factor [ 16 ].…”
Section: Discussionmentioning
confidence: 99%